PENYUSUNAN INSTRUMEN PENGENDALIAN PEMANFAATAN RUANG KAWASAN SEKITAR TPA REGIONAL ILO-ILO - Sekeon, Edwin Aldrin; Isnaeni, Arif; Manoppo, Gladis; Gunawan, Marihot Joseph (Department of Architecture, Engineering Faculty - Sam Ratulangi University, 2023)
ABSTRAK Pemanfaatan ruang dalam pelaksanaannya tidak selalu sejalan dengan rencana tata ruang yang telah ditetapkan. Hal ini disebabkan oleh beberapa faktor, di antaranya tekanan perkembangan pasar terhadap ruang, belum jelasnya mekanisme pengendalian, dan lemahnya penegakan hukum. Selain itu, dapat disebabkan juga karena produk rencana tata ruang yang kurang memperhatikan aspek pelaksanaan atau pemanfaatan ruang yang kurang memperhatikan rencana tata ruang. Maka, pengendalian pemanfaatan ruang sangat diperlukan untuk mewujudkan terciptanya pembangunan yang tertib tata ruang. Salah satu pelaksanaan pengendalian pemanfaatan ruang yang dilakukan berada di kawasan sekitar Tempat Pemprosesan Akhir (TPA) Sampah Regional Ilo-Ilo. Isu dan permasalahan di kawasan tersebut adalah terjadinya dominasi kegiatan pemanfaatan ruang yang tinggi seperti peruntukan permukiman dan perkantoran yang berpotensi melampaui daya dukung dan daya tampung peruntukan yang direncanakan. Kawasan sekitar TPA Sampah Regional Ilo-Ilo berdasarkan Peraturan Daerah Provinsi Sulawesi Utara Nomor 1 Tahun 2014 tentang Rencana Tata Ruang Wilayah Provinsi Sulawesi Utara Tahun 204-2034 memiliki peruntukkan ruang sebagai tanaman pangan, perkebunan dan tanaman tahunan. Agar pemanfaatan tata ruang dapat berjalan sesuai dengan rencana tata ruang maka diperlukan Instrumen Pengendalian Pemanfaatan Ruang. Instrumen Pengendalian Pemanfaatan Ruang di kawasan sekitar TPA Sampah Regional Ilo-Ilo menghasilkan 5 (lima) zona kendali kawasan. Setiap zona kendali kawasan memiliki peruntukkan kawasan, ketentuan intensitas pemanfaatan ruang, ketentuan tata bangunan, ketentuan sarana prasarana, dan pemberian insentif dan pemberian disinsentif. Kata Kunci: Pengendalian Pemanfaatan Ruang, Zona Kendali Kawasan, TPA Sampah Regional. ABSTRACT Spatial utilization in its implementation is not always in line with the established spatial plan. This is caused by several factors, including market development pressure on space, unclear control mechanisms, and weak law enforcement. In addition, it can also be caused by spatial planning products that pay less attention to aspects of implementation or spatial use that pay less attention to spatial planning. So controlling the use of space is very necessary to realize the creation of an orderly spatial development. One of the implementations of space utilization control done in the area around the Ilo-Ilo Regional Waste Final Processing Site (TPA). Issues and problems in the area are the domination of high spatial use activities such as the designation of settlements and offices which have the potential to exceed the carrying capacity and capacity of the planned designation. The area around the Ilo-Ilo Regional Waste TPA based on Regional Regulation of North Sulawesi Province Number 1 of 2014 about Spatial Planning for North Sulawesi Province Year 204-2034 has space allotment as food crops, plantations and annual crops. In order for the spatial utilization to run according to the spatial plan, a Space Utilization Control Instrument is needed. The Spatial Utilization Control Instrument in the area around the Ilo-Ilo Regional Waste TPA produces 5 (five) area control zones. Each area control zone has respective area designation, spatial use intensity provisions, building layout provisions, and infrastructure facility provisions as well as provision of incentives and disincentives. Keywords: Space Utilization Control, Area Control Zones, The Ilo-Ilo Regional Waste TPA